R&D and productivity in Finnish firms - Valmari Nelli (The Research Institute of the Finnish Economy (ETLA), 2022)
Productivity of the Finnish private sector decreased during the financial crisis of 2008-2009 and, since then, productivity growth has not reached the level preceding the crisis. A key factor underlying productivity growth is R&D. The population of Finnish firms, excluding Nokia, have increased their R&D inputs since the financial crisis. Therefore, it is worthwhile considering whether changes in productivity effects of R&D, instead of changes in volumes of R&D inputs, may explain the slowdown in productivity growth. This paper estimates productivity effects of Finnish firms' R&D inputs in several industries for the years 2001-2009 and 2010-2018. The estimates are used to find out whether the productivity effects of R&D have decreased after the financial crisis. The empirical strategy (Doraszelski and Jaumandreu, 2013) allows for productivity effects that are nonlinear and heterogeneous across firms. For most of the industries studied, there is no statistical evidence that the productivity effects of R&D are lower for the years 2010-2018 than for the years 2001-2009. Instead, there is evidence that, in some industries, the productivity effects of R&D increased after the financial crisis. In other words, low productivity growth after the financial crisis does not seem to be caused by a decrease in the productivity effects of R&D.
Keywords: D24; L60; O30; 330; R&D; Productivity; Production function estimation